Bright Polariton Coumarin‐Based OLEDs Operating in the Ultrastrong Coupling Regime. Issue 17 (25th June 2018) - Genco, Armando; Ridolfo, Alessandro; Savasta, Salvatore; Patanè, Salvatore; Gigli, Giuseppe; Mazzeo, Marco
Abstract: Organic microcavities in strong and ultrastrong light–matter coupling regimes allow the exploration of intriguing quantum phenomena, such as Bose–Einstein condensation of exciton‐polaritons, even at room temperature. Nevertheless, electrically driven organic polariton devices have shown so far poor performances, insufficient for practical applications, mainly due to the lack of an effective approach to exploit the molecular properties in order to optimize the population mechanism of polariton states. Here, novel bright polariton organic light‐emitting diodes (OLED) are reported based on a coumarin dye, which showed coupling strengths up to 37%, entering in the ultrastrong coupling regime. Owing to a high molecular emission efficiency, a large Stokes shift, and a fine cavity‐exciton tuning, the radiative pumping mechanism of polariton states has been fully optimized, leading a large portion of excitons to be converted in polariton emission. The resulting polariton OLEDs showed external quantum efficiencies up to 0.2% and maximum luminance of 700 cd m −2, which are, to the best of our knowledge, the highest values reported so far for this class of devices. Furthermore, the findings give clear indications for an effective exploitation of organic polariton dynamics toward the development of novel optoelectronic devices. Abstract : Organic microcavities in strong and ultrastrong light–matter coupling regimes allow the exploration of intriguing phenomena, such as Bose–Einstein condensation of exciton‐polaritons. This study presents novel bright polariton organic light‐emitting diodes based on a coumarin dye, reaching the ultrastrong coupling regime. The radiative pumping mechanism of polariton states is fully optimized, leading a large portion of excitons to be converted in polariton emission.